Monogenic diabetes – an unappreciated problem among physicians - Niechciał, Elżbieta; Skowrońska, Bogda; Gertig-Kolasa, Anna; Krzyśko, Izabela; Fichna, Piotr (Journal of Medical Science, 2014)
Monogenic diabetes results from one or more mutations in a single gene. It is a relatively rare genetic condition, therefore, it was frequently unappreciated among clinicians. Consequently, monogenic diabetes is misdiagnosed as type 1 diabetes or type 2 diabetes. Such misclassification leads to an inappropriate treatment, often inconvenient for the patients, such as insulin injections with their permanent glycemic control. The correct diagnosis may completely change previous methods of treatment. Patients diagnosed with GCK mutations may be completely treated with adequate diet. HNF1A/HNF4A affected patients are extremely sensitive to low dose sulphonylureas. Moreover, the exact diagnosis has an impact on patients’ relatives. Mostly, misdiagnosing of monogenic diabetes is caused by its rare occurrence and insufficient training in this area among physicians. According to different studies it may comprise 1–4% of all cases of diabetes. The aim of this article is to emphasize that despite the fact that monogenic diabetes is an uncommon disease, it should always be considered in cases of diabetes with unusual course.